Functional reversal of (−)‐Stepholidine analogues by replacement of benzazepine substructure using the ring‐expansion strategy. (24th June 2016) - Li, Wei; Zhang, Li; Xu, Lili; Yuan, Congmin; Du, Peng; Chen, Jiaojiao; Zhen, Xuechu; Fu, Wei
Abstract : (−)‐Stepholidine is an active ingredient of the Chinese herb Stephania and naturally occurring tetrahydroprotoberberine alkaloid with mixed dopamine receptor D1 agonistic and dopamine receptor D2 antagonistic activities. In this work, a series of novel hexahydrobenzo[4, 5]azepino [2, 1‐a]isoquinolines were designed and synthesized as ring‐expanded analogues of (−)‐Stepholidine. Initial pharmacological assays demonstrated that a benzazepine replacement was associated with significant increase in selectivity and functional reversal at dopamine receptor D1 . Compound‐(−)‐15e ( K i = 5.32 ± 0.01 nm ) is more potent than (−)‐Stepholidine ( K i = 13 nm ) and was identified as a selective dopamine receptor D1 antagonist (IC50 = 0.14 μ m ). Moreover, molecular modeling suggested that (−)‐15e might exert its dopamine receptor D1 antagonistic activities through interacting with the transmembrane helix 7 of dopamine receptor D1 . Abstract : A series of novel ring‐expanded analogues of (−)‐Stepholidine ( l ‐SPD) were designed, synthesized and bioassayed as potent ligands at D1R. Compound‐(− )‐15e ( K i = 5.32 ± 0.01 nm ) is more potent than l ‐SPD ( K i = 13 nm ) and was identified as a selective D1R antagonist (IC50 = 0.14 μ m ). This structural modification was associated with significant increase in selectivity and functional reversal at D1R in comparison with (−)‐ l ‐SPD with dual D1R agonistic and D2R antagonistic activities.